Produção de silagem de sorgo de diferentes aptidões em duas épocas de cultivo - Behling Neto, Arthur (2016)
Sorghum stands out among plants recommended for silage because of its intrinsic characteristics, as well as resistance to drought and seeding amplitude. There are on the market new grain and sweet sorghum cultivars which can be used for silage production, but lack information about their fermentation characteristics, nutritional value and digestibility. Goal was to evaluate the fermentation and chemical characteristics, and in vitro digestibility of different purpose sorghum silages, at two cropping seasons. Trial was conducted at the Plant Production Department of the Federal Institute of Education, Science and Technology of Rondônia, Colorado do Oeste campus, and chemical analyses and in vitro incubations were performed at the Laboratory of Animal Nutrition, at Federal University of Mato Grosso, Cuiabá campus. Experimental design was a randomized block, in spli-plot design, with four replications. Plot treatments consisted of six sorghum cultivars of different purpose (BRS 308 and BRS 310, grain sorghum; BR 655 and BRS 610, silage sorghum; BRS 506 and CMSXS 647, sweet sorghum). Split-plot treatments consisted of cropping seasons (first crop and second crop). Although not all sorghum cultivars presented ideal dry matter and water soluble carbohydrates content, all treatments showed pH and ammonia nitrogen content within the recommended limits, with good fermentation inside the silo. In sweet sorghum cultivars, a higher content of ethanol and butyric acid was observed, at first crop compared to the second crop. All evaluated sorghum cultivars can be used for silage production, but sweet sorghum use at first crop promotes silage with high levels of ethanol and butyric acid, being recommended for use at second crop. Forage sorghum cultivar BRS 655 showed higher non-fiber carbohydrate content and lower potentially digestible fiber. Sweet sorghum cultivars presented higher water soluble carbohydrates content, higher nonprotein nitrogen content based on protein, lower indigestible neutral detergent fiber content at second crop, and higher in vitro dry matter digestibility. Sweet sorghum cultivars are good options for silage production, but it is better recommendation at second crop. Forage sorghum cultivar BRS 655 is a good option for silage at both crops.